Acceptance and Use of LiVE Unpad in Vocational Education Student: Extended UTAUT-3 Approach - Fahmi, Muhammad Ainul; Nisa, Farhatun; Sukmadewi, Rani; Hasan, Zidny Ilma (Jurnal Teknologi Pendidikan, 2023)
The applied Learning Management System (LMS) method utilizes a blended learning model that combines synchronous and asynchronous methods. LiVE Unpad itself is an LMS used by Padjadjaran University which was developed to apply E-learning where lecturers and students carry out the teaching and learning process separately from distance, time, or both. Owing to the important role of students as end users of the LiVE Unpad, it is important to understand the factors affecting acceptance and use of LiVE Unpad. Therefore, this study is an effort to explore the acceptance and use of LiVE Unpad among vocational school students enrolled in Universitas Padjadjaran using UTAUT-3 approach. The result in this study shows that Perceived Pedagogical Value effects all endogenous variables. All variable in UTAUT-3 influenced the behavioural intention and use behaviour except the price value and personal innovativeness factors